2012
DOI: 10.3168/jds.2012-5346
|View full text |Cite
|
Sign up to set email alerts
|

Milk protein genetic variants and isoforms identified in bovine milk representing extremes in coagulation properties

Abstract: A gel-based proteomic approach consisting of 2-dimensional gel electrophoresis coupled with mass spectrometry was applied for detailed protein characterization of a subset of individual milk samples with extreme rennet coagulation properties. A milk subset with either good or poor coagulation abilities was selected from 892 Danish Holstein-Friesian and Jersey cows. Screening of genetic variants of the major milk proteins resulted in the identification of common genetic variants of β-casein (CN; A(1), A(2), B),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 37 publications
(70 reference statements)
9
75
1
Order By: Relevance
“…Variations in glycosylation degree of κ-CN and of κ-CN isoforms have been addressed in several studies (Dalgleish, 1986;Robitaille et al, 1991;Coolbear et al, 1996;Jensen et al, 2012a). In a recent larger study, no significant difference was observed between genetic variants, although κ-CN BB was found to have a slightly higher glycosylation degree compared with κ-CN AB and AA (Bonfatti et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Variations in glycosylation degree of κ-CN and of κ-CN isoforms have been addressed in several studies (Dalgleish, 1986;Robitaille et al, 1991;Coolbear et al, 1996;Jensen et al, 2012a). In a recent larger study, no significant difference was observed between genetic variants, although κ-CN BB was found to have a slightly higher glycosylation degree compared with κ-CN AB and AA (Bonfatti et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Some of the most important factors influencing coagulation properties are the total fat and protein contents, in addition to variability in protein composition and specific genetic variants of the caseins (Wedholm et al, 2006;Hallén et al, 2007;Jensen et al, 2012). Moreover, SCC, acidity (Ikonen et al, 2004), and variability in minor milk compounds, such as minerals and citrate (Udabage et al, 2001;Tsioulpas et al, 2007), have also been associated with differential milk coagulation properties.…”
Section: Introductionmentioning
confidence: 98%
“…Improvement of these traits can be achieved through selection for correlated traits such as milk protein content and composition (Bonfatti et al, 2011;Jensen et al, 2012), milk acidity (Ló pez et al, 1998; -E-mail: martino.cassandro@unipd.it Ná jera et al, 2003) and somatic cell count (SCC; Politis and Ng-Kwai-Hang, 1988;Klei et al, 1998). Moreover, genetic variants at the protein loci have been demonstrated to exert an effect on MCP (Kü barsepp et al, 2005;Comin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%